China's Rebalancing and Gender Inequality. (IMF Working Papers; Working Paper ;, 2021)
This paper examines gender inequality in the context of structural transformation and rebalancing in China. We document declining women's relative wages and labor force participation in China during the last two decades, despite rapid growth and expansion of the service sector. Using household data, we provide evidence consistent with a U-shaped relationship between economic development and women's labor market outcomes. Using a model of structural transformation, we show that labor market barriers for women have increased over time. Model counterfactuals suggest that removing these barriers and increasing service sector productivity can boost both gender equality and economic growth in China.